Fabrication of porous metallic glass using a dissolution manufacturing strategy and their functional applications - Junsheng Liu; Wenqing Ruan; Jianan Fu; Heting Zhang; Shenghao Zeng; Shuai Ren; Jiang Ma (Materials Today Advances)
Recent developments in the engineering of metallic glasses (MGs) with custom properties have been compelling, particularly in porous constructions. This review brings to the fore a dissolution manufacturing strategy as a cutting-edge modality for creating porous MGs, allowing precise control over their pore dimensions and configurations. The strategy was employed within various pH conditions—acidic, alkaline, and neutral—to produce materials with distinctive porosities. These materials exhibited exceptional mechanical merits including enhanced strength and improved resistance to fracture, as well as notable thermal endurance. Their versatility was further highlighted by their promising roles in catalysis, energy conversion, and biomedicine. The data suggest that these porous MGs stand out with superior attributes conducive to broad industrial deployment, heralding them as frontrunners for multifaceted applications. The dissolution manufacturing strategy surfaces as a trailblazing and streamlined route to engineer porous MGs, fostering the advancement of high-performance metallic composites.